KONSEP PENGEMBANGAN TERMINAL AGRIBISNIS DI KECAMATAN PENENGAHAN KABUPATEN LAMPUNG SELATAN (Jurnal Planesa (Planologi), 2016)
The Agribusiness Terminal Area in its prisnsip is an agricultural activity program that seeks to create agribusiness activities to learn the profit-making strategy by managing the aspect of cultivation, supply of raw materials, postharvest, processing, to marketing stage in a large activity in one region or region consisting of central- centers of production and trade, services. The problems that exist in the planning area are the limitations of the superior commodity processed products, the buying and selling process of the wholesalers. From the existing problems can be overcome with the development of agribusiness terminal where the marketing center and bargain buying and selling of goods or agricultural products can operate well and without going through the middleman, agribusiness terminal can facilitate the product quality mnyediakan place sorting and packaging, equipped with warehouses, to stage sales in the auction market as well as training farmers and traders handling the packaging of agricultural produce.Â Keywords: concept of agribusiness terminal development of Penengah subdistrict